PENGELOLAAN KEARSIPAN DI KANTOR DESA PALOAN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Septiyanti Riyan E.42008052 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This study examines issues related to how the existing archivalmanagement at the Village Office Paloan and constraints. The purpose of thisstudy was to determine the management of archives at the Village Office Paloanand barriers that exist in the management of archives at the Village Office Paloan.The conclusion of this study indicate that the management of archives atthe Village Office Paloan not been implemented to the maximum. It can be seenfrom the use of the diary are not accompanied by a disposition sheet, archivalstorage systems that are combined, using a card that does not control the form andthe files are damaged and dirty. For that recommendations made is for archivalstorage and placement shall be in accordance with their respective fields andsaved Dimap or plastic file box and an entry form and book lending for archivecontrol. Keywords: management, filing, storage and control.